ChemInform Abstract: Synthesis and Antiproliferative Evaluation of Novel Tetrahydrobenzo[4′, 5′]thieno[3′, 2′:5, 6]pyrido[4, 3‐d]pyrimidine Derivatives. Issue 7 (29th January 2015) - Tang, Chu; Liang, Yongju; Bai, Shun; He, Hongwu; Chen, Yu; Yang, Guangzhong; Fu, Liwu
Abstract It is found that some Schiff base compounds (XII) show similar or even stronger antiproliferative activity than the positive control Fluorouracil against KB and CNE2 cell lines.